A silence from Hitchcock - Pomerance, Murray, 1946- (State University of New York Press, 2023)
Extensive meditations on silence in the films of Alfred Hitchcock.
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation.; Hitchcock, Alfred, -- 1899-1980; Silence in motion pictures.; Silence au cinéma.; PERFORMING ARTS / Film & Video / History & Criticism.; Silence in motion pictures; Electronic books.; Criticism, interpretation, etc.